Development of a Citizen Science–Based Thermochemistry Module Oriented toward Scientific Literacy and Environmental Awareness - Rahmatiya Abdjul; Astin Lukum; Deasy Natalia Botutihe (Universitas Negeri Medan, 2026)
This study aimed to develop and evaluate a Citizen Science–based thermochemistry teaching module as an innovative learning resource in senior high school chemistry. The study employed a research and development design using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The participants were 119 eleventh-grade students from a public senior high school in Gorontalo. Data were collected through expert validation, teacher and student practicality questionnaires, scientific literacy tests, and environmental awareness questionnaires. The results indicated that the developed module achieved high validity and practicality and demonstrated effective learning outcomes, as reflected in improved scientific literacy and increased levels of environmental awareness after implementation. The novelty of this study lies in the integration of the Citizen Science approach into a thermochemistry module that explicitly connects abstract energy concepts with authentic environmental exploration activities, an area that has been rarely addressed in chemistry education research. These findings suggest that the developed module is feasible and pedagogically meaningful for supporting scientific literacy and environmental awareness in senior high school chemistry learning.